New faiths, old fears : Muslims and other Asian immigrants in American religious life - Lawrence, Bruce B. (American lectures on the history of religions (American Academy of Religion), 2002)
As a result of immigration from Asia in the wake of the passage of the 1965 Hart-Celler Immigration Act, the fastest-growing religions in America -- faster than all Christian groups combined -- are Islam, Hinduism, Buddhism, and Sikhism. Now a leading scholar asks how these new faiths have changed or have been changed by the pluralist face of American civil society and by the deep-rooted American ambivalence toward foreign traditions.